UTILIZATION OF RHIZOSPHERE FUNGI TO CONTROL Fusarium oxysporum f.sp. capsici IN VITRO - Sudarma, I Made; Puspawati, Ni Made; Suniti, Ni Wayan; Wijaya, I Nyoman; Bagus, I Gusti Ngurah (International Journal of Biosciences and Biotechnology; Vol 2 No 2 (2015))
Fusarium caused wilt disease in chilli pepper and destroyed some farmer crops. Results ofpreliminary research has been discovered that the disease caused by Fusarium oxysporum f.sp. capsici.The alternative environmental friendly method is to find antagonist microbes which is located in therhizosphere of healthy pepper plants. This study aims to find out potentially antagonistic fungi tocontrol Fusarium wilt disease on pepper plants. The fungi were isolated by soil dilution method orviable plate count method on Potato Dextrose Agar medium with antibiotic Livoplaxacin (25%, w/v).Rhizosphere fungi from healthy pepper plants had been identified. A total of 63 spesies belong to 4genera included Penicillium (45 species), Aspergillus (6 species), Trichoderma (9 species) andCandida (3 species). The highest percentage of distribution of rhizosphere fungi are P. digitatum(47.63%), P. expansum (19,05%), T. harzianum (9,53%), A. nidulans, A. niger, Penicillium sp.,Candida albicans, and T. vitrens i.e 4,76% respectively. All of rhizosphere fungi colonies were foundto inhibit Fusarium oxysporum f.sp. capsici in vitro. The best inhibition was found in Aspergillusniger at 88.89 ± 2.2% followed by A. nidulans of 85,56 ± 1,6 %, T. harzianum at 84,45 ± 1,58% , andT. virens by 83,33 ± 1,2%, five days after inoculation. All of them have a very high inhibition criteria.
Keywords: Rhizosphere fungi, Fusarium oxysporum f.sp. capsici, inhibiting ability, persentage contribution, and antagonistic